(untitled) (Praxis Educativa, 2026)
This essay analyzes the emergence of antifeminist, misogynistic, and homophobic discourses among students entering physical education teacher training programs, relating them to digital phenomena such as cybermasculinities and the manosphere. Based on a bibliographic review and situated teaching experiences, the text problematizes how digital platforms commodify masculinities in crisis, offering reactionary narratives that become naturalized in academic spaces historically permeable to masculinism. The work shows that Comprehensive Sexuality Education, while present throughout the educational trajectory of these populations, seems insufficient in the face of the reach of digital radicalization devices. The necessity to reopen the debate on feminisms, queer pedagogies, and disputes of meaning in teacher training careers is proposed, particularly in physical education.